2018
DOI: 10.1097/corr.0000000000000592
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Prevalence of Cam Deformity After Prophylactic Pinning of the Contralateral Asymptomatic Hip in Unilateral Slipped Capital Femoral Epiphysis? A 10-year Minimum Followup Study

Abstract: Background Prophylactic pinning of the asymptomatic and normal-appearing contralateral hip in patients with unilateral slipped capital femoral epiphysis (SCFE) remains controversial. Understanding the minimal 10-year clinical, functional, and radiographic outcomes of the contralateral asymptomatic hip in unilateral SCFE may be helpful in the decision regarding whether the benefits associated with potentially preventing a SCFE are outweighed by the risk of additional surgery. Questions/purposes Among patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 55 publications
1
38
0
Order By: Relevance
“…Mean age was 27 ± 7 years and 52 % were women ( Table 1 ). Of the included 31 hips, 7 hips(23 %) had a cam deformity [ 27 ], 5 hips(16 %) had a pincer deformity ( Table 1 ). Five hips(16 %) had cam deformity combined with decreased femoral version [ 28 ] while 7 hips(23 %) had increased femoral version [ 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Mean age was 27 ± 7 years and 52 % were women ( Table 1 ). Of the included 31 hips, 7 hips(23 %) had a cam deformity [ 27 ], 5 hips(16 %) had a pincer deformity ( Table 1 ). Five hips(16 %) had cam deformity combined with decreased femoral version [ 28 ] while 7 hips(23 %) had increased femoral version [ 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Measurement of femoral torsion was performed on standardized CT scans according to the method described by Lerch et al 24,26 and Murphy et al 35 This CT-based method showed a smaller variability and higher accuracy compared with other measurement methods 49 and compared with biplane radiographs for measurement of femoral torsion. 21 Cam-type deformity was defined as an alpha angle 25,39 greater than 50° on lateral radiographs in the presence of a normal acetabulum 61 (LCEA, 23°-33°). A cam-type deformity was present in 36% of the hips with protrusio acetabuli and in 37% of the hips with acetabular retroversion.…”
Section: Methodsmentioning
confidence: 99%
“…Although decreased FV can lead to an extra-articular conflict between the proximal femur and the anterior iliac inferior spine (AIIS) in patients with total hip arthroplasty and bipolar hemiarthroplasty, 47,48 it remains unclear whether the same condition leads to anterior intra-articular impingement, extra-articular subspine impingement, or an aggravation of a concomitant cam-type deformity in the native hip joint. 54,60 Cam-type FAI reduces internal rotation (IR) of the hip, 20,43 typically assessed in 90° of flexion. 60 Decreased FV also impairs IR 62 and thus may lead to anterior FAI in patients with slipped capital femoral epiphysis 20,24,64 and mechanical effect during IR of the hip joint.…”
mentioning
confidence: 99%
“…54,60 Cam-type FAI reduces internal rotation (IR) of the hip, 20,43 typically assessed in 90°of flexion. 60 Decreased FV also impairs IR 62 and thus may lead to anterior FAI in patients with slipped capital femoral epiphysis 20,24,64 and mechanical effect during IR of the hip joint. 62,63 Before the early description of FAI, decreased FV was described as a cause for hip pain and osteoarthritis, and rotational osteotomies to increase FV have been performed in adult patients.…”
mentioning
confidence: 99%